Recurrent ischemic stroke in atrial fibrillation with non-vitamin K antagonist oral anticoagulation. (June 2019) - Woo, Ho Geol; Chung, Inyoung; Gwak, Dong Seok; Kim, Baik Kyun; Kim, Beom Joon; Bae, Hee-Joon; Han, Moon-Ku
Highlights: Dosing methods of NOACs and MVO in recurrent cardioembolic stroke are associated. Reduced rate of MVO showed in patients who received standard dose of NOACs. Anticoagulation caused by missed or lowered doses of NOACs were associated with MVO. Abstract: The etiology or rate of recurrent ischemic stroke according to dosing methods including drug adherence in patients taking non-vitamin K antagonist oral anticoagulants (NOACs) remain uncertain. We investigated the association between dosing methods including drug adherence achieved with NOACs and the presence of major vessel occlusion (MVO) in patients with ischemic stroke with non-valvular atrial fibrillation (NVAF). From July 2013 through December 2016, 120 patients with recurrent ischemic stroke with NVAF on NOACs were retrospectively analyzed. Patients taking non-standard doses of NOACs were divided into the missed dose group that discontinued NOACs for ≥48 h prior to arrival, and the under-dose group that used lower doses of NOACs. A logistic regression analysis was performed to determine the association between MVO and dosing methods including drug adherence. There were 60 (50.0%), 39 (32.5%), and 21 (17.5%) patients, respectively, in the standard dose, under-dose, and missed dose groups. Twelve patients (20.0%) in the standard dose group, 15 (38.5%) in the under-dose group, and 13 (61.9%) in the missed dose group had MVO. MVO was significantly higher in the missed dose group than in the standard dose and under-dose groups ( P  = 0.002). In patients with ischemic stroke with NVAF, who are on NOACs, anticoagulation caused by missed or lowered doses of NOACs was significantly associated with MVO in patients with recurrent cardioembolic stroke.